The roles of communication and management of conflicts towards leadership: a study at Glenmarie Properties Sdn Bhd - Abdullah, Nurul Asma' (2017)
Leadership is an important function in an organization which helps to maximize efficiency and to achieve organizational goals. An effective leadership is needed in an organization to provide guidance and create healthy work environment to influence employees. In order to be effective leadership, good communication and conflict management seems to be associated. Therefore, the aim of this study is to investigate the roles of Communication and Management of Conflicts towards Leadership a study at Glenmarie Properties Sdn Bhd (GPSB). This research was aimed to achieve the following objectives; What is the relationship between communication and leadership; What is the relationship between management of conflicts and leadership; What is the strongest influence between communication and management of conflict with leadership. The population of this research is 94 staffs of GPSB and the sample size is 76. Convenience sampling has been used as sampling technique for this research. A self-developed questionnaire, measured on Likert scale was used to collect data from respondents. In general, the reliability of the variables are reliable as the Cronbach’s Alpha for all variables are more than 0.6. Moreover, the results have shown that Communication and management of conflicts have a significant relationship with Leadership. Thus far, the result will help the organization to increase the effectiveness of leader.